Fifteen-minute consultation: Management of the infant born to a mother with toxoplasmosis in pregnancy. Issue 5 (18th February 2020) - Saso, Anja; Bamford, Alasdair; Grewal, Karen; Noori, Muna; Hatcher, James; D'Arco, Felice; Guy, Edward; Lyall, Hermione
Abstract : Congenital toxoplasmosis occurs following transplacental transfer of Toxoplasma gondii . Irrespective of symptom status at birth, infants with congenital infection may develop serious long-term sequelae, including learning disability, seizures, hydrocephalus, motor and hearing deficits, chorioretinitis and retinal scarring with impaired vision. Timely diagnosis facilitates early initiation of therapy, aimed at prevention or amelioration of adverse clinical consequences. Diagnosis can be difficult, however, since acutely infected mothers are often asymptomatic and laboratory testing can be complex. Moreover, any decision to start treatment in the newborn must include careful consideration of the benefits and risks. This paper outlines a structured approach for managing an infant born to a woman with possible or confirmed T. gondii infection during pregnancy, including key aspects of the antenatal history, interpretation and timing of investigations, treatment and appropriate follow-up. Our recommendations are based on current evidence in the literature, consensus from two UK paediatric infectious disease centres and the UK specialist Toxoplasma Reference Unit.